APPLICATION OF ISLAMIC BUSINESS ETHICS IN COSMETIC SALES IN KENDARI CITY - Aswawi, Nurafiah; Wiyiatuti, Wiwiek; Syaranamual, Irelda Sari; Prafika Cahyani, Putri (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the application of Islamic business ethics principles in sales practices at Dzaky Kosmetik, a local cosmetics store in Kendari City. This research uses a qualitative descriptive research design to explore how Islamic business ethics are implemented in sales practices. A qualitative approach was deemed suitable as it allows an in-depth understanding of behaviors, values, and perceptions that cannot be quantified but are critical to evaluating ethical practices from an Islamic perspective. Data were collected through observation, interviews, and documentation. The results show that the principles of honesty (?idq) and balance (?adl) are implemented quite well, particularly in price transparency and product authenticity. However, the principles of unity (taw??d), free will (ikhtiy?r), and responsibility (am?nah) have not been implemented thoroughly. The lack of consumer education and the absence of a structured complaint mechanism are important weaknesses. This study concludes that a deeper internalization of Islamic values is needed to maintain ethical consistency and strengthen consumer trust in the business sector.